Tree Mortality Risks Under Climate Change in Europe: Assessment of Silviculture Practices and Genetic Conservation Networks - Petit-Cailleux, Cathleen; Davi, Hendrik; Lefèvre, François; Verkerk, Pieter Johannes; Fady, Bruno; Lindner, Marcus; Oddou-Muratorio, Sylvie (Frontiers in Ecology and Evolution, 2021)
Climate change can positively and negatively affect abiotic and biotic drivers of tree mortality. Process-based models integrating these climatic effects are only seldom used at species distribution scale. The main objective of this study was to investigate the multi-causal mortality risk of five major European forest tree species across their distribution range from an ecophysiological perspective, to quantify the impact of forest management practices on this risk and to identify threats on the conservation network. We used the process-based ecophysiological CASTANEA model to simulate the mortality risk of Fagus sylvatica, Quercus petraea, Pinus sylvestris, Pinus pinaster and Picea abies under current and future climate conditions, while considering local silviculture practices. The mortality risk was assessed by a composite risk index (CRIM) taking into account the risk of carbon starvation, hydraulic failure and frost damage. We took into account extreme climatic events with the CRIMmax, computed as the maximum annual value of the CRIM. The physiological processes' contributions to CRIM differed among species: it was mainly driven by hydraulic failure for P.sylvestris and Q.petraea, by frost damage for P. abies, by carbon starvation for P.pinaster, and by a combination of hydraulic failure and frost damage for F.sylvatica. Under future climate, projection showed an increase of CRIM for P.pinaster but a decrease for P. abies, Q.petraea and F.sylvatica, and little variation for P.sylvestris. Under the harshest future climatic scenario, forest management decreased the mean CRIM for P.sylvestris, increased it for P. abies and P.pinaster and had no major impact for the two broadleaved species. By the year 2100, 38% to 90% of the GCUs are at extinction threat (CRIMmax=1), depending on the species. Using a process-based ecophysiological model allowed us to disentangle the multiple drivers of tree mortality under current and future climate. Taking into account the positive effect of increased CO2 on fertilization and water use efficiency, the average risks may increase or decrease in the future depending on species and sites. However, considering extreme climatic events, future projections are as pessimistic than those obtained with bioclimatic niche models.